ΓT‐S195A thrombin reduces the anticoagulant effects of dabigatran in vitro and in vivo. (19th June 2014) - Sheffield, W. P.; Lambourne, M. D.; Eltringham‐Smith, L. J.; Bhakta, V.; Arnold, D. M.; Crowther, M. A.
Summary Background Dabigatran etexilate (DE) is an oral direct thrombin inhibitor used to prevent strokes in patients with atrial fibrillation. No licensed DE antidote is currently available. We hypothesized that active site‐mutated S195A thrombin (S195A‐IIa) and/or its trypsinized derivative (γT‐S195A‐IIa) would sequester dabigatran, the active form of DE, and reduce its anticoagulant effects. Objective To assess active site‐mutated S195A or γT‐S195A‐IIa as dabigatran reversal agents in vitro and in vivo. Methods Diluted thrombin time (dTT) assays were performed using human or murine plasma containing dabigatran, combined with S195A‐IIa, γT‐S195A‐IIa or FPR‐chloromethyl ketone‐treated thrombin (FPR‐IIa). Bleeding times were determined in anesthetized DE‐treated mice also receiving γT‐S195A‐IIa or vehicle 15 min prior to tail transection. The time to occlusion of carotid arteries of DE‐treated mice also receiving S195A‐IIa, γT‐S195A‐IIa, prothrombin complex concentrate (PCC) or vehicle, 15 min prior to topical FeCl3, was determined using Doppler ultrasound. Results γT‐S195A‐IIa reduced dTT values of dabigatran‐containing human and murine plasma more effectively than S195‐IIa; FPR‐IIa had no effect. A dose of 13 mg kg−1 DE abrogated occlusive thrombus formation in the carotid arteries of FeCl3‐treated mice; γT‐S195A‐IIa (6 mg kg−1) or PCC (14.3 IU kg−1), but not saline vehicle or S195A‐IIa (6 mg kg−1), was equally effective in restoring thrombus formation. Bleeding times of mice treated with 60 mg kg−1 DE and γT‐S195A‐IIa (6 mg kg−1) or saline vehicle did not differ. Conclusions Our data suggest that γT‐S195A‐IIa decreases the anticoagulant effects of dabigatran in vitro and is partially effective at restoring hemostasis‐related thrombus formation in DE‐treated mice in vivo.